Dowry deaths: Response to weather variability in India. - Storeygard, Adam.; Sekhri, Sheetal. (Tufts University. Tisch Library., 2017)
We examine the effect of rainfall shocks on dowry deaths using data from 583 Indian districts for 2002-2007. We find that a one standard deviation decline in annual rainfall from the local mean increases reported dowry deaths by 7.8%. Wet shocks have no apparent effect. We examine patterns of other crimes to investigate whether an increase in general unrest during economic downturns explains the results but do not find supportive evidence. Women's political representation in the national parliament has no apparent mitigating effect on dowry deaths.